Gastroesophageal Reflux Disease and Its Associations with Depression, Other Psychiatric Disorders and Patient Quality of Life: A Literature Review - Szerocki, Jan; Milewska-Plis, Katarzyna; Winkowska, Alicja; Grudina, Alina; Kłak, Igor; Grodzicka , Joanna; Bartnik, Katarzyna; Herian, Mariola; Karalus, Monika; Curyło, Weronika (Quality in Sport, 2025)
Gastroesophageal reflux disease (GERD) is a prevalent gastrointestinal disorder whose incidence has been increasing in recent years. Due to its potential extraesophageal manifestations, diagnosing GERD can be challenging. Emerging evidence suggests that GERD may have significant implications not only in the digestive tract, including effects on mental health. This review investigates the potential associations between GERD and psychiatric disorders such as depression, anxiety, bipolar disorder and sleep disturbances, as well as its impact on quality of life and productivity. Relevant literature was found through databases including PubMed, ResearchGate and Google Scholar with a focus on meta-analyses and systematic reviews. The findings indicate that GERD is associated with a higher risk of mental health disorders, particularly depression and sleep disorders. These relationships may be bidirectional. Additionally, recent studies highlight promising non-pharmacological interventions that may alleviate GERD symptoms. Understanding the psychological consequences of GERD and integrating mental health screening into gastroenterological practice could potentially improve patient outcomes. However, further research is needed to clarify the mechanisms linking GERD and mental health.